Some considerations on the current shape of the tenant’s pre-emptive right to agricultural property in the light of the Act on shaping the agricultural system - Blajer, Paweł Andrzej (Przegląd Prawa Rolnego, 2019)
The purpose of the considerations is to attempt to determine the current status of the tenant’s pre-emptive right resulting from the Act on shaping the agricultural system, taking into account the amendments introduced by the Act of 26 April 2019. The author states that the amendments to the pre-emptive right of the lessee, or tenant, of an agricultural property should, in principle, be assessed positively. They have widened the scope of objects of tenant’s pre-emptive rights, which nevertheless still remain rather narrow, while the regulation of the statutory pre-emptive right of the lessee raises many practical doubts. In the author’s opinion, a lease should be treated as a factual instrument to improve the agrarian structure of the country. A normative model of agricultural leases should be developed, which would include a rationally formed pre-emptive right of the lessee of the property.